Republic of Kazakhstan : Financial Sector Assessment Program Update-Technical Note-Investment Opportunities for Pension Funds. (IMF Staff Country Reports; Country Report ;, 2004)
This technical note examines investment opportunities for pension funds in Kazakhstan. It puts forward policy alternatives that could lead to improved management of pension fund assets in Kazakhstan. The note emphasizes prudence in the management of pension assets, given the social and fiscal importance of the pension sector. It discusses different investment alternatives and development options for the domestic Kazakhstan capital market. The note concludes that neither the regulators nor industry participants appear to fully appreciate the risks attached to the practice of focusing on short-term and high-yield investments.